Impact of the carbon pore size and topology on the equilibrium quantum sieving of hydrogen isotopes at zero coverage and finite pressures - Kowalczyk, Poitr; Gauden, P.; Terzyk, A.; Furmaniak, S. (IOP Publishing Ltd, 2009)
Carbonaceous slit-shaped and square-shaped pores efficiently differentiate adsorbed hydrogenisotopes at 77 and 33 K. Extensive path integral Monte Carlo simulations revealed that thesquare-shaped carbon pores enhanced the selectivity of deuterium over hydrogen in comparisonto equivalent slit-shaped carbon pores at zero coverage as well as at finite pressures(i.e. quantum sieving of hydrogen isotopes is pore-topology-dependent). We show that thisenhancement of the D2/H2 equilibrium selectivity results from larger localization of hydrogenisotopes in square-shaped pores. The operating pressures for efficient quantum sieving ofhydrogen isotopes are strongly dependent on the topology as well as on the size of the carbonpores. However, for both considered carbon pore topologies the highest D2/H2 separation factoris observed at zero-coverage limit. Depending on carbon pore size and topology we predictedmonotonic decreasing and non-monotonic shape of the D2/H2 equilibrium selectivity at finitepressures. For both kinds of carbonaceous pores of molecular sizes we predict highcompression of hydrogen isotopes at 77 and 33 K (for example, the pore density of compressedhydrogen isotopes at 77 K and 0.25 MPa in a square-shaped carbon pore of size 2.6 °A exceeds60 mmol cm-3; for comparison, the liquid density of para-H2 at 30 K and 30 MPa is42 mmol cm-3). Finally, by direct comparison of simulation results with experimental data it isexplained why ‘ordinary’ carbonaceous materials are not efficient quantum sieves.